The Relationship of Depression with Sleep Quality in Psychology Students of Unika Atma Jaya University During the Covid-19 Pandemic - Juan Feivel Stevanus (Jurnal Health Sains, 2021)
Exotropia sensory is unilateral divergence as a sequel to vision loss or long-standing poor vision. Characterized by large angles, comitant strabismic, increased gradually. Surgical characteristic treatment success are final deviation less than 10 prism diopters at distance in the primary position. Large deviation requires operating on three or four horizontal muscle and operating only for poor vision. This research aims to report the exotropia sensory patients and the result of surgical treatment for sensory exotropia by examiningthe outcomes of the surgical treatment. This is a prospective descriptive study conducted from January 2018 to December 2020 at Dr.M.Djamil hospital, Padang. A total of 12 patients included in this study. Detailed history regarding the complaint, developmental history was taken. Patients were thoroughly evaluated for visual acuity, through anterior segment evaluation using slit lamp, and fundus examination, and finding the deviation of the eye by doing hisberg test and prisma krimsky near and distance test. The result of surgical treatment evaluated by examine Hirsberg test and prisma krimsky test. A total of 12 patient were included, of whom   6 cases (50%) are man and woman 6 cases (50%), and the patients are 21-30 age year old about 33,33%.  From the etiology, retinal abnormalities are the most causes of the exotropia with 4 cases (33,33%). The patient are management by surgical and with monocular reses-resect hang back surgery. From 6-month follow up, the patient was satisfactory cosmetic result with orthotropia 85,71%. The patient exotropia sensory are 21-30 years old. The most common cause of sensory strabismus was retinal abnormalities, and the long-term outcome of surgery for sensory exotropia was satisfactory.